Enhancing Daylight and Improving Energy Usage through the Utilization of Lightshelves in Deep Plan Office Buildings in Dubai - Al Waary, Thuraya Hael (2012)
A city like Dubai that is ever growing with a constant need and demand for more energy, one can only think of solutions to mitigate this issue. Introducing daylight into office buildings can bring about major benefits to human health and comfort as well as reduce energy consumption levels. The use of daylighting is a key strategy for energy reduction as well as improving the quality of light in an interior environment. However, introducing daylight into deep plan office buildings remains a challenge when relying only on regular windows and skylights. Therefore, this study looks at the employment of lightshelves as an innovative strategy to penetrate daylighting into the office space. In order to calculate the effect of having lightshelves into a space, a modeling simulation was performed through IESVE. An important aspect about the office modules is that it included a dimming profile that was set to 300 lux. This profile worked through the placement of sensors within the space. Sensors simply measured light penetration, and then shifted the dependency on electrical lighting to daylighting. This process helped in the reduction of energy consumption levels vastly. The proposed lightshelves with light dimming profiles have achieved the most energy savings in the south orientation which resulted in 22.6%.However when assessing the study of different plan depths results for 5x5m show greatest reductions and light penetration due the small depth of the space. The 5x10m was considered the most ideal depth and reduction for the study achieving a maximum of 22.6%. The addition of the lightshelves has benefited the office modules energy efficiency which was confirmed through the placement of lightshelf heights. The 0.5m height from the roof revealed the highest reductions reaching 25.1% serving as a shading device and blocking internal heat gain from entering the space. The placement of openings in the lightshelves between cases of 1, 2 and 3 openings no significant change in energy consumption was observed. Therefore, this analysis is likely not sensitive enough for studying the number of openings on the lightshelf. However both exterior projections and interior depths of the lightshelves effected light penetration and energy reductions in the study. The energy benefit from the shading effect is more desirable with a longer projection in the exterior. As for the total energy, the 2m exterior projection showed 22.6% reductions. While the interior depth of the lightshelves determined that a climate like Dubai would always benefit from the most shading, the highest total energy reductions remained at the 7.5m and 5m at 22.6%. The combined analysis was then tailored for the optimum energy reduction levels. The total energy consumption revealed 24.5% which showed the highest and most ideal amongst the rest of the cases. From the study, an important aspect that came across was that earlier in the morning findings confirmed that the building was not under direct solar load from the glazing. A general conclusion that was derived is that each kW of reduction in light energy is likely to save around a kW in cooling energy. In conclusion, using lightshelves with a light dimming system confirmed energy reductions in office modules located in the city of Dubai, while allowing light deeper into the interior space.